White‐Light Generation Upon In‐Situ Amorphization of Single Crystals of [(Me3P)3AuSn(PhSn)3S6] and [(Et3P)3AgSn(PhSn)3S6]. Issue 12 (2nd April 2019) - Dornsiepen, Eike; Dobener, Florian; Mengel, Nils; Lenchuk, Olena; Dues, Christof; Sanna, Simone; Mollenhauer, Doreen; Chatterjee, Sangam; Dehnen, Stefanie
Abstract: In order to gain more information on the white‐light generation by amorphous molecular materials, the influence of metal complex substituents on the photophysical properties of potential white‐light emitters is investigated. Three compounds of the general type [(R3 P)3 MSnPhSn3 S6 )], with R/M = Me/Au (1 ), Et/Ag (4 ), and Me/Cu (5 ), are produced by reactions of the organotin sulfide cluster [(PhSn)4 S6 ] (A ) with the corresponding coinage metal complexes [M(PR3 )3 Cl]. Excess of the gold complex in the reaction leads to rearrangement and formation of [Au(PMe3 )4 ][Au(PMe3 )2 ][(PhSnCl)3 S4 ] (2 ). The use of PMe3 instead of PEt3 in the reaction with the silver salt causes decomposition and affords [(Me3 P)3 AgSnCl3 ] (3 ). All compounds are structurally characterized, and the necessity of sterically stabilizing PEt3 groups at the silver complex in 4 are rationalized by density functional theory (DFT) calculations. Measurements of the photophysical properties of 1, 4, and 5 show that the introduction of the metallo‐ligands indeed affects the materials properties, and at the same time confirm that the reduction of the molecular symmetry alone is not a sufficient condition for white‐light generation (WLG), which still requires amorphicity of the compound. This is realized for 1 and 4 in situ, while reabsorption processes inhibit WLG in case of the copper compound 5 . Abstract : New molecular materials with extreme nonlinear optical properties based on adamantane‐type organotin sulfide clusters are reported, allowing for more insight into their still unknown potential for white‐light generation (WLG). Experimental and theoretical studies on [(R3 P)3 MSn(PhSn)3 S6 ] (R = Me, Et; M = Cu, Ag, Au) show the influence of different metallo‐ligands on material properties and the potential for WLG upon in‐situ amorphization.